2020
DOI: 10.2528/pierc19112603
|View full text |Cite
|
Sign up to set email alerts
|

Improved Isolation Metamaterial Inspired Mm-Wave Mimo Dielectric Resonator Antenna for 5g Application

Abstract: A rectangular Dielectric Resonator Antenna (DRA) four element Multiple in Multiple Out (MIMO) is proposed for 5G application, and each element is supplied with slot-coupled microstrip feed. The entire construction has a dimension of 20 mm × 40 mm. Four Dielectric Resonators are mounted exactly above the slot. In order to improve the isolation, metamaterial is printed on top of the dielectric resonators, which move away the solidest coupling fields. As the metamaterial structure interacts with electromagnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It is observed that the the proposed MIMO antenna with metasurface array outperforms the other reported works in terms of isolation. Moreover, the antenna gain exhibited by proposed MIMO antenna is significantly higher than the works [32,34,36,38,39,40]. Although the works presented in [35,37] achieved higher gain as compared to the proposed antenna, however, these MIMO structures have only two elements, and also MIMO performance analysis is not provided.…”
Section: Comparison With the Related Workmentioning
confidence: 80%
See 2 more Smart Citations
“…It is observed that the the proposed MIMO antenna with metasurface array outperforms the other reported works in terms of isolation. Moreover, the antenna gain exhibited by proposed MIMO antenna is significantly higher than the works [32,34,36,38,39,40]. Although the works presented in [35,37] achieved higher gain as compared to the proposed antenna, however, these MIMO structures have only two elements, and also MIMO performance analysis is not provided.…”
Section: Comparison With the Related Workmentioning
confidence: 80%
“…In recent years, metamaterials have been investigated extensively owing to their various electromagnetic characteristics not commonly present in natural materials [33]. Several works reported mm-wave MIMO antennas with metamaterial structures to enhance the antenna performance, particularly reduction in mutual coupling or antenna gain improvement [34][35][36][37][38][39][40]. The work in [34] proposed a 2×2 mm-wave MIMO antenna with bi-layered Frequency Selective Surface (FSS) superstrate for addressing the mutual coupling effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, lot of research has been done on metamaterials due to their electromagnetic properties do not present in the natural materials [33]. Few mm-wave antennas utilizing a metamaterials concept, specifically focusing on gain improvement have been reported in [34][35][36][37][38]. In [34], a bowtie shaped antenna for the mm-wave band holding a MIMO configuration is presented.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed antenna yields a maximum bandwidth of 1 GHz while the size of the antenna after employing EBG surface becomes 27.5x27.5 mm 2 . Likewise, in [36], a DRA with four port MIMO antenna is proposed for the mm-wave band. For the gain enhancement purpose, a metamaterial surface is used on the top of DRA surface which gives a maximum gain of 7 dB for the desired operating band .…”
Section: Introductionmentioning
confidence: 99%